THE EFFECT OF TAXPAYER AWARENESS, TAX SANCTIONS, FISCAL SERVICE QUALITY, AND EDUCATION LEVEL ON INDIVIDUAL TAXPAYER COMPLIANCE AT KPP PRATAMA CIREBON DUA. - Meilinda, Riska; Lindya, Lindya; Firasati, Aoliyah (Al-Makki Publisher, 2024)
The purpose of this study was to investigate the effects of taxpayer awareness, tax sanctions, the quality of fiscal services, and education level on individual taxpayer compliance at the Cirebon Dua Primary Tax Service Office. This type of research is a type of basic research. The population of interest in this study comprises all individual taxpayers registered at the Cirebon Dua Primary Tax Service Office in 2023, totaling 547,405 taxpayers. This study employs the simple random sampling technique for sample selection. Primary data was collected through distributing questionnaires to respondents. Data analysis utilized multiple linear regression conducted with SPSS Version 25 software. The results showed that taxpayer awareness, fiscal service quality, and education level increased individual taxpayer compliance at KPP Pratama Cirebon Dua. However, it was found that tax sanctions had no effect on individual taxpayer compliance.